Sukcesy fińskiego systemu edukacji, czyli dlaczego Finlandia szczyci się jednym z najlepszych systemów szkolnictwa na świecie – porównawcze studium przypadku - Czujko-Moszyk, Ewelina (Studia Edukacyjne, 2018)
This paper seeks to answer the question why Finland is considered to have one of the best education systems in the world. The author aims at providing a descriptive case study of Finland in comparison to the Polish educational system with some reference to other Western countries. The world first noticed Finland following the release of PISA results in 2001. Yet, PISA overview is just a starting point for this case study. The paper analyses different social, economic and political factors which, in the author’s opinion, contributed the most to the Finnish success in education. Major arguments for the Finnish success are preceded by an overview of educational reforms from the 1950s until the present. The author argues that the remarkably high social status of teachers, their autonomy and great qualifications,consistency in educational reforms which offer high quality, equity and decentralization are the primary reasons for Finland’s global success. All of the above achievements are compared to Poland’s current situation in education.